2016
DOI: 10.1016/j.virep.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of LINE-1 retrotransposition by a human SAMHD1 polymorphism

Abstract: The HIV-1 restriction factor SAMHD1 has the ability to negatively modulate retrotransposition of the long interspersed element 1(LINE-1). By exploring the ability of human SAMHD1 polymorphisms to inhibit LINE-1, we found that the single nucleotide polymorphism S33A present in the Korean population lose the ability to inhibit LINE-1 retrotransposition. Because SAMHD1 residue S33 is phosphorylated in human cycling and non-cycling cells, we demonstrated that SAMHD1 requires to be either phosphorylated on position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In another study, it was found that SAMHD1 binds to ORF2p at the stage of the L1 RNP functional complex; moreover, the inhibitory activity of SAMHD1 against L1 is regulated by phosphorylation of threonine 592, the dephosphorylation of which correlates with the repression of L1 [121]. In addition to this site, another polymorphic site S33 phosphorylation was identified, which contributes to the inhibition of L1 [348]. As shown in a recent work, SAMHD1 is a nucleocytoplasmic shuttling protein and thus is possibly involved in the inhibition of L1 in the cytoplasm and nucleus, and the presence of SAMHD1 in the cytoplasm contributes to a decrease in ORF2p [349].…”
Section: Interferon-induced Factors Inhibiting the Formation Of L1 Rnpmentioning
confidence: 99%
“…In another study, it was found that SAMHD1 binds to ORF2p at the stage of the L1 RNP functional complex; moreover, the inhibitory activity of SAMHD1 against L1 is regulated by phosphorylation of threonine 592, the dephosphorylation of which correlates with the repression of L1 [121]. In addition to this site, another polymorphic site S33 phosphorylation was identified, which contributes to the inhibition of L1 [348]. As shown in a recent work, SAMHD1 is a nucleocytoplasmic shuttling protein and thus is possibly involved in the inhibition of L1 in the cytoplasm and nucleus, and the presence of SAMHD1 in the cytoplasm contributes to a decrease in ORF2p [349].…”
Section: Interferon-induced Factors Inhibiting the Formation Of L1 Rnpmentioning
confidence: 99%
“…Surprisingly, phosphomimetic mutations of T592 abolish the antiretroviral activity, but do not affect dNTP hydrolysis in vitro or in cells, which raises questions about the exact relationship between dNTP depletion and the restriction of retroviral replication 23 , 25 , 27 . It is also unclear whether and how the dNTPase activity contributes to other, less well-understood biological functions of SAMHD1, such as its roles in the DNA double-strand break repair 35 , interferon signaling 36 38 , restriction of LINE-1 retroelements 39 41 , degradation of nascent DNA at stalled replication forks 42 , and posttranscriptional control of mRNAs in regulatory T cells 43 . Involvement of nucleic acids in these distinct cellular activities suggests that the interaction of SAMHD1 with nucleic acids 44 49 may contribute to its function.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these experiments suggested that AGS observed in individuals with TREX1 mutations is triggered by the inability of TREX1 protein to degrade reverse-transcribed DNA from endogenous retroelements that are left in the cell, triggers the innate immune response. Moreover, it has recently been shown that SAMHD1 is involved in the restriction of endogenous retroelements in cycling cells and that this regulation is controlled by T592 phosphorylation, suggesting that the absence of SAMHD1 allows accumulation/replication of retroelements, which could trigger AGS or autoimmune diseases (Goodier, 2016; Herrmann et al, 2018; White et al, 2016; Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%